Adolescent Family Dynamics and the Role of Social Media in Shaping Relationships - Ahmadi Shooli , Zahra; Rahimi , Leili (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aims to explore the relationship between adolescent family dynamics and social media use. Methods and Materials: A qualitative research design was employed, with data collected through semi-structured interviews with 18 adolescents aged 14–18 and their parents, all residing in Tehran. The interviews explored adolescents’ social media usage patterns, family interactions, and the perceived impact of family relationships on digital behavior. Data were analyzed using NVivo software to identify recurring themes related to family dynamics, emotional support, and communication patterns. Findings: The study found that adolescents from families with strong communication, emotional support, and low conflict reported healthier social media usage and fewer mental health issues related to online behaviors. In contrast, adolescents from families with higher levels of conflict or limited emotional support exhibited higher levels of problematic social media use, including excessive time online, anxiety, and negative self-esteem. The results also suggested a bidirectional relationship between family dynamics and social media behaviors, where adolescents’ online experiences could influence family interactions, leading to conflicts over boundaries and supervision. Conclusion: The study concludes that family functioning plays a significant role in shaping adolescents’ social media behaviors and mental health outcomes. Positive family dynamics, including open communication and emotional support, can act as protective factors, helping adolescents manage the pressures of social media use. This highlights the importance of fostering healthy family environments to mitigate the risks associated with excessive social media engagement among adolescents.